An Experimental Investigation on Joining of Copper and Stainless Steel by Induction Welding Technique - Bhogendro Meitei, R. K.; Maji, Pabitra; Samadhiya, Ashutosh; Karmakar, Ranit; Ghosh, Subrata Kumar; Saha, Subhash Chandra (International journal of precision engineering and manufacturing, 2020)
The Cu–SS welded structures are widely used in nuclear and power generation industries. Various solid state and fusion welding techniques have been experimented for welding Cu–SS with resultant phenomena of low joining strength in solid state and generation of crack in fusion. Of late application of induction heating as a joining technique is gaining momentum in view of its low maintenance, high production rate and cost effectiveness. In consideration of the above facts, in this study, induction heating for welding Cu–SS is experimented in ambient condition under varied settings of load and current. Although few micro-cracks were observed in SEM images, successful joining between copper and stainless steel was achieved. Some compounds like FeCu 4 , Cr 3 Fe, Cu(Fe 2 O 4 ) and CrO were detected by XRD near the weld interface. The microhardness increased near the interface in comparison to the base metals. The interface microhardness was increased with current and load. Similarly, the tensile strength was also increased for higher values of process parameters. Highest strength of 220 MPa was obtained at 2 kg load and 650 A current. Failure of welded joint under tension took place by ductile–brittle fracture mode.